Clickbait as a Potential Threat in the Development of Cybercrime in Indonesia - Vanessa, Victoria; Ibrahim, Aji Lukman (JURNAL USM LAW REVIEW, 2024)
This research examines the advancement and extensive diffusion of online news in Indonesia which contains discrepancies between the titles displayed and the content displayed (clickbait), where the content has the potential to contain backlinks that can carry a cybercrime. The purpose of this research is to assess the potential of clickbait in threatening the development of cybercrime in Indonesia, as well as to investigate the best legal regulations for eradicating clickbait in Indonesia. This research uses the normative legal research method followed by the interview method. The outcomes of this research point to the shift in news media from conventional to online making the target of online news journalists not only limited to reporting factual information but also pursuing a target audience of readers by using a clickbait title. The content of clickbait news that clearly does not match the title can deceive Indonesians, especially if accompanied by backlinks that actually spread many forms of cybercrime. In addition, it was found that there are no regulations in Indonesia that prohibit the dissemination of online news with clickbait, be it in the Press Law, ITE Law, Journalistic Code of Ethics, Cyber Media Reporting Guidelines, and the Criminal Code, which can be overcome by revising the ITE Law by adding related prohibitions in Article 28.